Gene action for quantitative traits through Generation means analysis in sesame (Sesamum indicum) - JATOTH, JAWAHAR LAL; DANGI, KULDEEP SINGH; KUMAR, S SUDHEER (The Indian Journal of Agricultural Sciences, 2014)
Understanding the nature of gene action in the breeding material is helpful for breeders in formulating breeder strategy. In order to understand the type of gene action operating in the breeding materials six generation means (P1, P2, F1, F2, BC1 and BC2) from five crosses were used to estimate the genetic effects of yield and some quantitative traits in sesame (Sesamum indicum L.) The analysis showed the presence of additive, dominance and epistatic gene interactions. The additive dominance model was adequate for capsule length in the KMR 108 × JCS 507 and KKS 98049 × IS 562 B crosses. An epistatic digenic model was assumed for the remaining crosses. Duplicate- type epistasis played a greater role than complementary epistasis. The study deciphered that simple additive dominance model exhibited lack of good fit for all the traits in five crosses studied, indicating the role of non-allelic interactions. Dominance and epistatic interactions played a major role in the inheritance of yield and yield contributing characters in sesame. It can be categorically stated that reciprocal recurrent selection or diallel selective mating system are the need of the hour to modify the genetic architecture of sesame for attaining higher yields with desirable oil content.